MENGUKUR EFEKTIVITAS PEMBELAJARAN DARING DITINJAU DARI ASPEK FASILITAS, EKONOMI DAN SUMBER DAYA MANUSIA MAHASISWA - Kristianus Jago Tute; Lely Suryani (Program Studi Pendidikan Matematika, 2022)
The problem in research during the covid-19 period is that the face-to-face learning system has turned into online learning. Many digital platforms are used for this learning, one of which is e-learning used by the University of Flores. However, only some lecturers use online learning. The purpose of this study was to measure the effectiveness of online learning during the Covid-19 pandemic for students of mathematics education at the University of Flores in terms of facilities, economics and human resources. The method used in this research is a survey method with a descriptive quantitative approach. The population in this study were students of mathematics education at the University of Flores. A sample of 185 students in semester 2, 4, 6 and 8 were taken randomly. The data collection technique used a questionnaire in the form of a Likert scale. Data analysis used simple linear regression. The results of data analysis and hypothesis testing in this study indicate that the facility greatly influences the economy and human resources, the economy affects human resources. Conclusion The effectiveness of distance learning during the covid 19 pandemic on mathematics education students at the University of Flores is very effective from the aspect of facilities, economy and human resources used.